2007
DOI: 10.1016/j.bmc.2006.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Ring substituent effects on biological activity of vinyl sulfones as inhibitors of HIV-1

Abstract: In a previous study, we prepared a small library of chicoric acid analogs that possessed both potent anti-integrase and antiviral activity. It was also shown that active compounds fell into one of two groups: those that inhibited an early stage in viral replication and those that inhibited at a later stage. In this study, a series of vinyl geminal disulfone-containing compounds possessing a range of ring substituents has been synthesized to probe the impact of structure on inhibitory mechanisms. Four active co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(35 citation statements)
references
References 15 publications
0
34
0
1
Order By: Relevance
“…The noncharged nature of the sulfone improves cellular penetration over ionizable mimics such as l-chicoric acid (Hadd et al, 2001;Meadows et al, 2005;Meadows & Gervay-Hague, 2006a). The vinyl sulfone groups in the compounds reported in this study, (I)-(IV), have been shown to be an important class of antivirals, with the possibility for covalent attachment (Meadows & Gervay-Hague, 2006b;Meadows et al, 2007). As part of these ongoing inhibition studies, we previously reported the structures of the saturated phosphonate monosulfone diisopropyl (diisopropoxyphosphorylmethylsulfonylmethyl)phosphonate and the disulfone diisopropyl (diisopropoxyphosphorylmethylsulfonylmethylsulfonylmethyl)phosphonate (Wong, Olmstead, Fettinger & Gervay-Hague, 2007) reagents, which are the starting materials for the title compounds.…”
Section: Commentmentioning
confidence: 83%
“…The noncharged nature of the sulfone improves cellular penetration over ionizable mimics such as l-chicoric acid (Hadd et al, 2001;Meadows et al, 2005;Meadows & Gervay-Hague, 2006a). The vinyl sulfone groups in the compounds reported in this study, (I)-(IV), have been shown to be an important class of antivirals, with the possibility for covalent attachment (Meadows & Gervay-Hague, 2006b;Meadows et al, 2007). As part of these ongoing inhibition studies, we previously reported the structures of the saturated phosphonate monosulfone diisopropyl (diisopropoxyphosphorylmethylsulfonylmethyl)phosphonate and the disulfone diisopropyl (diisopropoxyphosphorylmethylsulfonylmethylsulfonylmethyl)phosphonate (Wong, Olmstead, Fettinger & Gervay-Hague, 2007) reagents, which are the starting materials for the title compounds.…”
Section: Commentmentioning
confidence: 83%
“…Dapsone (4, 4'diaminodiphenylsulphone), an antileprotic drug which is a sulfone analog, has been proved to be a powerful antimicrobial agent 16 . Sulfone derivatives provide an example of a vital class of bioactive compounds with a wide spectrum of activities, as the sulfone group is a fundamental found in diverse biologically active compounds with a vast range of biological activity including antifungal 17 , herbicidal 18 , anti-hepatitis 19 , antitumor 20 , antileprotic 21 , anti-inflammatory 22 , anticancer 23 , anti-HIV-1 24 and anti-tubercular 25 properties. So, our present study is aimed at studying the interaction details between Enoyl-ACP reductase and sulfone class of compounds.…”
Section: Preparation Of Ligandsmentioning
confidence: 99%
“…As part of our research into enzymes that are involved in the metastatic potential of tumor cells, a number of potential disulfone inhibitors for HIV-integrase have been identified (Meadows et al, 2005, Meadows & Gervay-Hague, 2006, Meadows et al, 2007. The monosulfone reagent reported here was envisioned and synthesized by a modification of the disulfone reaction (Hadd, et al, 2001).…”
Section: S1 Commentmentioning
confidence: 99%